Learning Strategies in PAUD to Stimulate Early Childhood Gross Motor Development - Fairuz Afra Rafifah; Feli Anissa; Firda Alfira Muklis; Suci Utami Putri (Penerbit Hellow Pustaka, 2024)
Learning strategies in PAUD to stimulate gross motor development have several strategies such as developmental aspects, approaches and movement development. The aim of this research is to determine learning strategies in PAUD to stimulate gross motor development in early childhood. The research method uses qualitative research with a literature study research design. Based on the research results, there are strategies that can be used to develop children's gross motor skills, such as outdoor activities, dance, gymnastics, traditional games, central learning models, learning methods based on aud gross motor development and circuit training activities.